2015
DOI: 10.1590/0104-1169.0098.2665
|View full text |Cite
|
Sign up to set email alerts
|

Ethical problems experienced by oncology nurses

Abstract: Objective: to know the ethical problems experienced by oncology nurses. Method: descriptive and exploratory study with a qualitative approach, performed in inpatient units and in chemotherapy out-patients units that provide assistance to oncological patients in two capitals in the South region of Brazil. Eighteen nurses participated in this study, selected by snowball sampling type. For data collection, semi-structured interviews were carried out, which were recorded and transcribed, and then analyzed by thema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 21 publications
2
15
0
11
Order By: Relevance
“…which reported that not only physicians but also nurses and other HCPs may encounter different ethical dilemmas [42,[44][45][46]47]. The demographic characteristics of our HCPs showed that the majority of our participants were female (79.5%).…”
Section: Plos Onementioning
confidence: 76%
See 1 more Smart Citation
“…which reported that not only physicians but also nurses and other HCPs may encounter different ethical dilemmas [42,[44][45][46]47]. The demographic characteristics of our HCPs showed that the majority of our participants were female (79.5%).…”
Section: Plos Onementioning
confidence: 76%
“…Nurses and other HCPs, who have the primary responsibility of caring for the patient, are somewhat more alert to the dilemmas associated with patients' well-being and dignity. Similarly, Norberg et al observed that nurses are more emotionally involved in ethical dilemmas concerning patient care compared to physicians [45][46][47][48][49][50].…”
Section: Plos Onementioning
confidence: 99%
“…A importância do enfermeiro no seu papel educativo, através do diálogo com o paciente, orientando e elucidando as dúvidas acerca do diagnóstico e tratamento, bem como, ouvindo a manifestação da sua decisão, tornam-se fatores determinantes para a qualidade do cuidado ao paciente com câncer. Importante sinalizar os princípios da integralidade e da autonomia, ou seja, a capacidade do ser humano de decidir sobre algo, de acordo com seus valores, expectativas, necessidades, prioridades e crenças 21,22 .…”
Section: Os Enfermeiros E a Práxis Junto àS Picsunclassified
“…One of the studies describes the complex task of palliative sedation in cases of extreme suffering, which results in a shock of values between patient, family and health team 26 . Doctors and nurses are uncertain about the ideal time to discuss the end of life and the clinical balance between the physician's emotional involvement and the patient's wishes 32,37 . Opinions of physicians about requests of patients at the end of life, their willingness to comply with requests such as retention of intubation, application of increasing doses of drugs are related to experience in the area, with substantial change during residency 33 .…”
Section: Dialogue Between Oncology and Bioethicsmentioning
confidence: 99%
“…The formal medical school curriculum or continuing medical education can be a way of learning to improve the communication between doctor and patient, and to increase the bioethical knowledge of the health professional. However, this education can not be restricted to theoretical content, but also to practice and Interfaces, gaps and challenges between bioethics and oncology http://dx.doi.org/10.1590/1983-80422018263265 experience [14][15][16]25,27,30,32,34 . It is also worth mentioning the need for studies on training strategies, their influence on medical performance and the impact on the quality of ethical decisions 33 .…”
Section: Gaps and Challenges For Future Dialoguesmentioning
confidence: 99%